Diagnostic challenges in the diagnosis and treatment of ovarian cancer in Lynch syndrome - Agnieszka Protasiuk; Agata Żak; Rafał Sierzpowski; Patrycja Tymoszuk; Bartosz Kasperek; Katarzyna Augustowska (Journal of Education, Health and Sport)
Introduction and purpose